Crecimiento y ciclos de la economía colombiana (2005 – 2019) (2020)
In 2005-19 Colombian economic growth was outstanding at the international level: GDP per worker increased 2.07% per year, equivalent to 36% in those 15 years. This was possible because total factor productivity (TFP) increased. This can be affirmed in view of the fact that capital stock, in the long term, is not an explanatory factor. What was worrying was the declining trend in the growth rate of TFP; in fact, it has stagnated in the last two years. Regarding to short run dynamics, Colombian business cycles depended on the United States´s cycles both directly and through the oil price. But the intensity of the Colombian cycles (their relative distance between peaks and troughs) was greater than the exhibited by American cycles.